The Subscription Based Trading : (Muhammadiyah Perspective) - Rizaldi, Ardhansyah Dwiki; Azka Muhammad, Rifqi (Indonesian Journal of Islamic Economic Law, 2025)
The objective of this study is to analyze the islamic legal aspects of buying and selling subscribers from the perspective of Muhammadiyah fatwa manhaj (methodology). The phenomenon of buying and selling subscribers has become widespread with the development of digital platforms such as YouTube, where subscribers have become one of the main requirements for monetization. This practice raises legal questions, particularly regarding its validity in Islam. Using qualitative approach by combining content analysis and literature review methods conducted based on Muhammadiyah methodological approach of tarjih, this study examines the practice of buying and selling subscribers based on Islamic principles such as honesty (as-sidq), justice (al-'adālah), and public interest (al-maslahah). The analysis reveals that this practice contains elements of deception, fraud, injustice, and gharar (uncertainty), which are contrary to Islamic business ethics. Therefore, by applying the Muhammadiyah fatwa methodology, such as the three-leveled approach to norms in Islamic law (al-qiyām al-asāsiyyah, al-uṣūl al-kulliyyah, and al-aḥkām al-farʻiyyah), it can be concluded that the buying and selling of subscribers is not permitted in Islam. This study is expected to serve as a reference for Muslims, especially in avoiding business practices that contradict Shari'a law.